Complex degree of coherency inherent to laser images of blood plasma polycrystalline networks - Ushenko, Yu.A.; Istratiy, V.V.; Dubolazov, A.V.; Angelsky, A.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Given in this paper are theoretical basics for correlation-phase analysis of laser
images inherent to human blood plasma. Also presented are comparative results of
measurements aimed at coordinate distributions of the module of complex degree of
coherency (CDC) and complex degree of mutual polarization (CDMP) of laser images
describing blood plasma of a healthy person as well as of a patient with prostate cancer
of the first stage. The authors investigated both values and ranges of changing the
statistical (moments of the first to fourth orders), correlation (coefficients of the GrammCharlie
expansion for autocorrelation functions) and fractal (slopes and dispersion of
extremes for logarithmic dependences of power spectra) parameters for coordinate
distributions CDC and CDMP. Determined are objective criteria for diagnostics of cancer
changes in blood plasma of a patient with cancer.